DIGITAL MARKETING COMPETENCE OF MIDDLE-MEDIUM BUSINESS PLAYERS (UKM) IN KECAMATAN LEMBANG WEST BANDUNG DISTRICT - Yulia Segarwati; Siti Fatimah; Yanti Purwanti (JEES: Journal of Economic Empowerment Strategy, 2020)
The economic development and digital marketing provide opportunities as well as challenges for SMEs in Indonesia. This especially provides an opportunity for SMEs to promote at a low cost while penetrating the market by cutting the product distribution channel to the final consumers. The presence of ICTs needs to be coupled with the ability of human resources (HR), in this case SMEs in Lembang District, West Bandung Regency. The digital marketing competence of these SMEs is important in developing small and medium businesses that enable potential customers to obtain information about products as well as transact through the internet. The research method was carried out by means of a survey with data collection techniques through questionnaires, interviews, and secondary data sources. The questionnaire was distributed to SMEs in Lembang District, West Bandung Regency with a sampling technique, and interviews were conducted with informants which were conducted selectively. The results of the study showed that the knowledge, attitude skills of SMEs are competencies that need to be improved. Digital marketing competence of SMEs in Lembang District, West Bandung Regency requires strengthening to encourage increased knowledge, attention to new knowledge through technology and media, making innovation and creativity in running their business through digital marketing skills, so that SMEs can optimally carry out their business by utilizing digital marketing. Digital marketing competence of SMEs in West Bandung Regency, especially in Lembang District does not yet have the level of ability needed to improve business performance, because the ability of adaptation and the ability to take advantage of opportunities, especially in technological development needs to be provided facilitation and retrieval from related parties, such as the government, universities, and other related organizations.